On the land of my father : a farm upbringing in segregated Mississippi - Exposé, Bevelyn Charlene, 1939- (McFarland & Company, Inc., Publishers, 2014)
"This book evokes a time and place that no longer exists but which is central to the American experience. The main message is of how land ownership bonded a Negro family to its white neighbors in segregated southern Mississippi in the 1940s. Working the land was not all pain and hostility. "--